Phytochemical Screening, Chemical Constitutions, and Antibacterial Activity for three Medicinal Plants Against Multidrug-Resistant Bacteria - Mathkoor, Maryam Mansoor (Technium BioChemMed, 2024)
Due to the importance of therapeutic plants in the production and preparation of drugs, The purpose of this study is to extract three medicinal plants, including seeds of Syzygium aromaticum “S. aromaticum”, leaves of Thymus vulgaris (T. vulgaris) and Myrtus communis (M. communis) using the steam distillation method. It evaluated their ability to inhibit pathogenic and antibiotic-resistant bacteria, including Staphylococcus aureus (S.aureus), Pseudomonas aeruginosa (P. aeruginosa), and Escherichia coli (E.coli) isolated from skin ulcers. Moreover, these extracts were cured to evaluate their phytochemicals and chemical constitutions using classical methods and Gc-mass spectroscopy. The phytochemicals results showed that the Flavonoids and terpenoids were observed in all samples, while the Alkaloids didn't appear. The extracts of S. aromaticum, T. vulgaris, and M. communis showed interesting compounds during the GC-mass spectroscopy test. It showed the presence of chemical compounds with active groups that could have a significant role in bacterial treatment, such as 9-octadecenamide, Caryophyllene, and Limonene. Moreover, The results of the bacterial test showed a high effectiveness of these oils on the types of bacteria used, especially S. aureus, and E. coli, where the highest results were for Myrtus on E. coli bacteria with an inhibition diam of 56 mm, while clove oil did not show any effectiveness against S. aureus, the inhibition zone diameter is zero. In general, the effectiveness of these essential oils against Gram N. P.aeruginosa was very weak compared to the effectiveness of these essential oils on other bacterial species used in the study, where the highest diameter of inhibition of these bacteria was by clove oil and reached 15 mm.